Oxidative Stress in Health and Disease - V. Prakash Reddy (Biomedicines, 2023)
Oxidative stress, resulting from the excessive intracellular accumulation of reactive oxygen species (ROS), reactive nitrogen species (RNS), and other free radical species, contributes to the onset and progression of various diseases, including diabetes, obesity, diabetic nephropathy, diabetic neuropathy, and neurological diseases, such as Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), and Parkinson’s disease (PD). Oxidative stress is also implicated in cardiovascular disease and cancer. Exacerbated oxidative stress leads to the accelerated formation of advanced glycation end products (AGEs), a complex mixture of crosslinked proteins and protein modifications. Relatively high levels of AGEs are generated in diabetes, obesity, AD, and other I neurological diseases. AGEs such as Ne-carboxymethyllysine (CML) serve as markers for disease progression. AGEs, through interaction with receptors for advanced glycation end products (RAGE), initiate a cascade of deleterious signaling events to form inflammatory cytokines, and thereby further exacerbate oxidative stress in a vicious cycle. AGE inhibitors, AGE breakers, and RAGE inhibitors are therefore potential therapeutic agents for multiple diseases, including diabetes and AD. The complexity of the AGEs and the lack of well-established mechanisms for AGE formation are largely responsible for the lack of effective therapeutics targeting oxidative stress and AGE-related diseases. This review addresses the role of oxidative stress in the pathogenesis of AGE-related chronic diseases, including diabetes and neurological disorders, and recent progress in the development of therapeutics based on antioxidants, AGE breakers and RAGE inhibitors. Furthermore, this review outlines therapeutic strategies based on single-atom nanozymes that attenuate oxidative stress through the sequestering of reactive oxygen species (ROS) and reactive nitrogen species (RNS).